Summary of over Fifty Years with Brain-Computer Interfaces-A Review - Kawala-Sterniuk, Aleksandra; Browarska, Natalia; Al-Bakri, Amir; Pelc, Mariusz; Zygarlicki, Jaroslaw; Sidikova, Michaela; Martinek, Radek; Gorzelanczyk, Edward Jacek (Brain sciences, 2021)
Over the last few decades, the Brain-Computer Interfaces have been gradually making their way to the epicenter of scientific interest. Many scientists from all around the world have contributed to the state of the art in this scientific domain by developing numerous tools and methods for brain signal acquisition and processing. Such a spectacular progress would not be achievable without accompanying technological development to equip the researchers with the proper devices providing what is absolutely necessary for any kind of discovery as the core of every analysis: the data reflecting the brain activity. The common effort has resulted in pushing the whole domain to the point where the communication between a human being and the external world through BCI interfaces is no longer science fiction but nowadays reality. In this work we present the most relevant aspects of the BCIs and all the milestones that have been made over nearly 50-year history of this research domain. We mention people who were pioneers in this area as well as we highlight all the technological and methodological advances that have transformed something available and understandable by a very few into something that has a potential to be a breathtaking change for so many. Aiming to fully understand how the human brain works is a very ambitious goal and it will surely take time to succeed. However, even that fraction of what has already been determined is sufficient e.g., to allow impaired people to regain control on their lives and significantly improve its quality. The more is discovered in this domain, the more benefit for all of us this can potentially bring.
Keywords: Brain-Computer Interfaces; signal processing methods; electrocorticography; neuro-imaging; electroencephalography